Technology adoption strategies in the supply chain: The case of Nguyen Nguyen Nguyenetnamese young small and medium-sized enterprises - Quang Thanh Ngo; Ngoc-Phuc Doan; Thanh-Hai Thi Tran; Tien Dung Nguyen (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The paper, using a three-wave unbalanced panel of 3252 observations of young small and medium-sized firms in 2011-2013, examines the effect of direct linkages between firms with foreign direct investment and young small and medium-sized firms on technology adoption strategies and the further influence of technology transfers from such linkages on technology adoption strategies. Moreover, the paper analyzes the extent that economic obstacles may cause young small and medium-sized firms to choose different adoptions. Our analysis shows that exporting firms do not tend to conduct embodied backward/forward adoptions, but more likely adopt the embodied backward purchasing. In addition, the impact of competitiveness follows an inverse U-shaped pattern for the embodied backward adoption, but a U-shaped pattern for the disembodied adoption. In terms of market power, there exists an inversed U-shaped pattern for the embodied backward adoption. Under the impact of foreign direct investment (FDI) linkages and vertical spillovers, it is found that technology transfer through backward/forward linkages is associated with the embodied ones, whereas a linkage with FDI domestic customers/suppliers is less likely associated with the embodied ones. In addition, under technology transfer, firms facing economic constraints may overcome these by looking for other financial sources and embodied technology transfer. The paper suggests the path for FDI firms, young small and medium-sized enterprises (SMEs), and technology adoption strategies in the future.
Keywords: 650; disembodied adoption; embodied backward adoption; embodied backward purchasing; embodied forward adoption; embodied forward purchasing; supply chain; technology adoption; Vietnam; young small and medium-sized firms